EVALUASI TINGKAT PENGETAHUAN OBAT ANTIDIABETES PADA MASYARAKAT DI DESA BONTOKASSI GOWA - Bayu Putra; Rachmat Kosman; Andi Maulana Kamri Petta Lolo (As-Syifaa Jurnal Farmasi, 2021)
Diabetes mellitus is one of disease caused by changes individual's lifestyle and is not in accordance with a healthy lifestyle. In addition, this is also caused by factors that cannot be ignored. Knowledge of the general public in rural areas is very minimal because of their ignorance about diabetes mellitus. The method used in this study is descriptive observational prospectively by providing a questionnaire to assess the level of knowledge of respondents and the use of diabetes medication. Data collection was carried out in two stages. As a result of this service activity, respondents who were given counseling actually experienced an increase in their understanding of diabetes. The data obtained were analyzed by statistical program with t-test analysis. This can be seen from the statistical results that there is an effect of p <0.05 on knowledge about diabetes, the use of antidiabetic drugs, the effectiveness of antidiabetic drugs, the quality of antidiabetic drugs, and adherence to taking antidiabetic drugs. With these changes, the importance of information on patients by pharmacists in the area is very important.